Design and engineering expertise are the training of future engineers (Pedagogy of Higher and Secondary Education, 2014)
Tsvirkun L. O. Design and engineering expertise are the training of future engineers.The article describes the scientific concept of «expertise», «professional competence» and «design and engineering expertise of the future engineer» refine the concepts used in the aspect of the competency approach concretized terms and given the author's definition of design competence as an integral part of professional readiness of the future engineer.
Keywords: engineer; competence approach; expertise; professional competence; design and engineering expertise of the future engineer; graphic discipline